PEMANFAATAN KITOSAN UNTUK MEMPERPANJANG UMUR SIMPAN BUAH PEPAYA VARIETAS CALIFORNIA - YUKI FIRMANSYAH; RASWEN EFENDI; RAHMAYUNI RAHMAYUNI (Universitas Riau, 2016)
The aims of this study is to study the effect of chitosan coating on papaya during storage and to obtain achitosan concentration that appropriate to extend the self life of papaya varieties california. The design ofthis study was a Block Randomized Design (BRD) with five treatments and four groups in order to obtaintwenty experiment units. The treatments in this study were the concentration of chitosan solution, includingK0: (control), K1: 0.5%, K2: 0.75%, K3: 1% and K4: 1.25%. Observations were made on days 0; 5; 10 and 15on weight loss, texture, total soluble solids, vitamin C and total plate count. The observation of respirationrate was performed on days 0 and 5. The data obtained were statistically analyzed using Analysis of Variance(ANOVA). If the F count is greater than or equal to F table then continued with Duncan’s New Multiple RangeTest (DNMRT) at 5% level. The utilization of chitosan coating significantly affect weight loss, respirationrate, texture, total dissolved solids, vitamin C and total plate count. The best treatment was based on theparameters that have been tested was papaya with chitosan concentration of 1.25% (K4). The results showedpapaya varieties california stored up to 15 days experienced a weight loss of 7.55%, texture 10.20 kgf/cm2,total dissolved solids 19.63p brix, vitamin C 15.58 mg and total plate count not detected. While the respirationrate of K4 treatment on day 5 was12.07 mg CO2/kg/hour.